Comparison of ruminal microbiota, IL-1β gene variation, and tick incidence between Holstein × Gyr and Holstein heifers in grazing system - Quirino, Daiana Francisca; Marcondes, Marcos Inácio; Oliveira, Kellen Ribeiro de; Guimarães, Simone Elisa Facioni; Silva, Juliana Soares da; Suen, Garret; Rossi, Letícia Elisa; Cunha, Camila Soares; Mantovani, Hilario Cuquetto; Rotta, Polyana Pizzi (Frontiers in Microbiology, 2024)
The variation in bacterial communities among breeds has been previously reported and may be one of the reasons why Holstein × Gyr dairy heifers have better development in grazing systems in tropical conditions. This study aimed to explore the ruminal microbiota composition, the IL -1 β gene variation, tick incidence, and blood parameters of Holstein × Gyr (½ Holstein × ½ Gyr) and Holstein heifers grazing intensely managed Guinea grass (Panicum maximum Jacq. cv Mombaça).Methods: Sixteen heifers were divided into two groups consisting of 8 Holstein × Gyr and 8 Holstein heifers.The experimental period was comprised of 3 periods of 21 d. Ruminal samples were taken via the stomach tube technique. The sequencing of the V4 hypervariable region of the 16S rRNA gene was performed using the Illumina MiSeq platform. Counting and collection of ticks were conducted each 21 d. Blood and skeletal muscle tissue biopsies were performed at the end of the experiment.Results: Firmicutes were the most abundant phyla present in both breed rumen samples and Bacteroidota showed differences in relative abundance between breed groups, with greater values for Holstein heifers (P < 0.05 with FDR correction). The 10 most abundant unique OTUs identified in each breed included several OTUs of the genus Prevotella. Holstein heifers had a greater tick count and weight (9.8 ticks/animal and 1.6 g/animal, respectively) than Holstein × Gyr (2.56 ticks/animal and 0.4 g/animal, respectively). We found nucleotide substitutions in the IL -1 β gene that might be related to adaptation and resistance phenotypes to tick infestation in Holstein × Gyr heifers. Blood concentrations of urea, albumin, insulin-like growth factor 1, triiodothyronine, and thyroxine were greater in Holstein × Gyr than in Holstein heifers.Adaptations in Holstein × Gyr heifers such as ruminal microbiota, tick resistance, nucleotide substitutions in IL -1 β gene, and hormone concentration suggest a better energy metabolism and thermoregulation resulting in better performance in tropical grazing systems.